The Criminal Act on Religion in Indonesia with Syari’Ah Perspective - Aprilianda, Nurini (2017)
The Seminar of National Law I of 1963 had been fundamental of issuing the Statute Number 5 of 1965 on the Prevention of Religion Misuse and/or Stigmatization (then called the Statute of PNPS). The Indonesian nation to have the Criminal code truly reflected the soul of Pancasila still continues. Therefore, it needs various comprehenship discussions, such as by discovering the values of Islamic Law, for a long time became one of material sources in formulation of National Law. The purpose of applying the Islamic Law (maqshid asy-Syari’ah) also insists that protecting religion (hifdhuddin) becomes the main purpose. The right to believe in a religion and to give opinion allowed by the statute are non derogable, however, there are limitations allowed by the statute (permissible restriction), because certain reasons such as “protection of human right and other freedom”. To bring about the First Principle and Act 29 of the Fundamental Constitution of 1945 of Republic Indonesia, it needs Penal Effort to protect religion from misuse. Keywords: Syari’ah, criminal act on religio